Amino Acid Fermentation - Yokota, Atsushi; Ikeda, Masato (Springer Japan : Imprint: Springer, 2017)
This book presents the latest findings on amino acid fermentation and reviews the 50-year history of their development. The book is divided into four parts, the first of which presents a review of amino acid fermentation, past and present. The second part highlights selected examples of amino acid fermentation in more detail, while the third focuses on recent advanced technologies. The last part introduces readers to several topics for future research directions in amino acid production systems. A new field, "amino acid fermentation", was created by the progress of academic research and industrial development. In 1908, the Japanese researcher Kikunae Ikeda discovered glutamate as an Umami substance. Then a new seasoning, MSG (monosodium glutamate), was commercialized. Although glutamate was extracted from the hydro-lysate of wheat or soybean in the early days, a new production method was subsequently invented - "fermentation" - in which glutamate is produced from sugars such as glucose by a certain bacterium called Corynebacterium. The topic of this volume is particularly connected in a significant way with biochemical, biotechnological, and microbial fields. Both professionals in industry and an academic audience will understand the importance of this volume.
Keywords: Life sciences.; Biotechnology.; Food -- Biotechnology.; Microbiology.; elektronické knihy; electronic books